The Implementation of Restorative Justice for Misdemeanor Crimes after Perpol No. 8 of 2021 - Sjuhudi, Ichsan; Musahib, Abd Razak (PT. Anagata Sembagi Education, 2025)
This study analyzes the application of restorative justice to minor crimes in the Indonesian criminal justice system, especially after the issuance of Police Regulation No. 8 of 2021. The shift from a retributive approach to a restorative approach is a response to the failure of the conventional criminal system in achieving substantive justice and overcrowding in correctional institutions. The research method used is normative juridical with a statutory and conceptual approach. The results of the study show that restorative justice has strong theoretical legitimacy through the concept of reintegrative shaming and normative support from Law No. 11 of 2012 and Perpol No. 8 of 2021. However, its implementation faces juridical and institutional challenges, especially related to the hierarchy of norms, accountability, and the understanding of law enforcement officials and the public towards the concept of restorative justice. It also found potential irregularities if there is no strict supervision of the peace mechanism outside the formal process. Therefore, there is a need for harmonization of regulations, integrated training for officials, and the participation of civil society in the supervision of implementation. This study recommends the reform of the Criminal Code and the establishment of inter-institutional regulations to ensure that restorative justice becomes a valid, effective, and just approach in national criminal law enforcement.